Effect of elevated CO2 on carbon partitioning in young Quercus ilex L. during resprouting - Aranjuelo, Iker; Pintó-Marijuan, Marta; Avice, Jean Christophe; Fleck, Isabel (Rapid Communications in Mass Spectrometry, 2011)
Stored carbon (C) represents a very important C pool with residence times of years to decades in tree organic matter. With the objective of understanding C assimilation, partitioning and remobilization in 2-year-old Quercus ilex L., those trees were exposed for 7 months to different [CO2] (elevated: 700 µmol mol−1; and ambient: 350 µmol mol−1 CO2). The 13C-isotopic composition of the ambient CO2 (ca. −12.8‰) was modified (to ca. −19.2‰) under the elevated CO2 conditions in order to analyze C allocation and partitioning before aerial biomass excision, and during the following regrowth (resprouting). Although after 7 months of growth under elevated [CO2], Q. ilex plants increased dry matter production, the absence of significant differences in photosynthetic activity suggests that such an increase was lower than expected. Nitrogen availability was not involved in photosynthetic acclimation. The removal of aboveground organs did not enable the balance between C availability and C requirements to be achieved. The isotopic characterization revealed that before the cutting, C partitioning to the stem (main C sink) prevented leaf C accumulation. During regrowth the roots were the organ with more of the labelled C. Furthermore, developing leaves had more C sink strength than shoots during this period. After the cutting, the amount of C delivered from the root to the development of aboveground organs exceeded the requirements of leaves, with the consequent carbohydrate accumulation. These findings demonstrate that, despite having a new C sink, the responsiveness of those resprouts under elevated [CO2] conditions will be strongly conditioned by the plant's capacity to use the extra C present in leaves through its allocation to other organs (roots) and processes (respiration). Copyright © 2011 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd
Keywords: carbon allocation; Cutting; Elevated CO2; leaves; Photosynthetic activity (voyant); Regrowth; roots